Revisiting differences between atopic and non-atopic asthmatics: When age is shaping airway inflammatory profile - Sara Gerday, MSc; Florence Schleich, MD, PhD; Monique Henket, MSc; Françoise Guissard, MSc; Virginie Paulus, MSc; Renaud Louis, MD, PhD (World Allergy Organization Journal, 2022)
Background: Atopic asthma is one of the most common asthma phenotypes and is generally opposed to the non-atopic counterpart. There have been very few large-scale studies comparing atopic and non-atopic asthmatics in terms of systemic and airway inflammation across the age spectrum. Methods: Here, we have undertaken a retrospective study investigating 1626 patients (924 atopic and 702 non-atopic asthmatics) recruited from our university asthma clinic who underwent extensive clinical investigations including induced sputum. Atopy was defined by any positive specific IgE to common aeroallergens (>0,35 kU/L). We performed direct comparisons between the groups and sought to appreciate the influence of age on the airway and systemic inflammatory components. The study was approved by the ethics committee of the University Hospital of Liege (Ref. 2016/276). Informed consents were obtained from healthy subjects. Results: Atopic asthmatics were younger (P < .001), had a higher male/female ratio (P < .001), an earlier disease onset (P < .001) and a greater proportion of treated rhinitis (P < .001) while non-atopic asthmatics had greater smoke exposure (P < .001), lower FEV1/FVC ratio (P = .01) and diffusing capacity (P < .001). There was no difference between the 2 groups regarding FEV1 (% predicted), asthma control, asthma quality of life and exacerbations in the previous 12 months. Regarding inflammation, atopic patients had higher FeNO levels (median = 28 ppb, P < .001), were more eosinophilic both in blood (median = 2.8%, P < .001) and in sputum (median = 2.2%, P < .001) while non-atopic patients displayed greater blood (median = 57%, P = .01) and sputum (median = 58.8%, P = .01) neutrophilic inflammation. However, stratifying patients by age showed that non-atopic asthmatics above 50 years old became equally eosinophilic in the sputum (P = .07), but not in the blood, as compared to atopic patients. Likewise, FeNO rose in non-atopic patients after 50 years old but remained, however, lower than in atopic patients. Conclusions: We conclude that, while sharing many features, atopic group still differentiates from non-atopic asthmatics by demographics, functional and inflammatory profiles. When atopic asthmatics showed a constant eosinophilic pattern across the age spectrum, non-atopic asthmatics were found to be neutrophilic before the age of 50 but eosinophilic above 50 years old.